2002
DOI: 10.1002/adfm.200290007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Family of Boron‐Containing Hole‐Blocking Amorphous Molecular Materials for Blue‐ and Blue–Violet‐Emitting Organic Electroluminescent Devices

Abstract: A novel family of amorphous molecular materials that function as hole blockers in organic electroluminescent (EL) devices, tris(2,3,5,6‐tetramethylphenyl)borane (TPhB), tris(2,3,5,6‐tetramethylbiphenyl‐4‐yl)borane (TBPhB), tris(2,3,5,6‐tetramethyl‐1,1′;4′,1″‐terphenyl‐4‐yl)borane (TTPhB), and tris[4‐(1,1′;3′,1″‐terphenyl‐5′‐yl)‐2,3,5,6‐tetramethylphenyl]borane (TTPhPhB), have been designed and synthesized. They readily form stable amorphous glasses with high glass‐transition temperatures, and are characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 45 publications
1
64
0
3
Order By: Relevance
“…[3][4][5][6][7] Owing to the above-mentioned features, TABs are used as emitting and/or charge-transport materials in optoelectronic devices, such as organic light-emitting diodes (OLED). [1,2,[8][9][10] In particular the combination of TABs with Abstract: We synthesized a series of amino substituted triarylboranes (TABs) 1-3 by copper(i)-catalyzed cross-coupling reactions. The title compounds were investigated by means of cyclic voltammetry (CV) and UV-visible absorption and fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Owing to the above-mentioned features, TABs are used as emitting and/or charge-transport materials in optoelectronic devices, such as organic light-emitting diodes (OLED). [1,2,[8][9][10] In particular the combination of TABs with Abstract: We synthesized a series of amino substituted triarylboranes (TABs) 1-3 by copper(i)-catalyzed cross-coupling reactions. The title compounds were investigated by means of cyclic voltammetry (CV) and UV-visible absorption and fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Since a decade, boron-based materials have been the focus of numerous researches, especially devoted to Organic Electronics as these materials exhibit a remarkable electron mobility due to the vacant p-orbital of the boron atom [74][75][76]89,90]. Triarylboron derivatives are also characterized by their bulkiness and these materials are also strong electron withdrawing groups.…”
Section: Triarylborane Emittersmentioning
confidence: 99%
“…[29] We observed that the EL emission was dominated by the emission of rubrene ( Figure S3, Supporting Information), confirming the effectiveness of the host-guest energy transfer. We deposited a hole-transport/electron-blocking layer of N,N′-bis(3-methylphenyl)-N,N′-diphenylbenzidine (TPD) [30] from solution for the first time. This simply prepared layer effectively reduces exciton quenching by the MoO x / Au anode.…”
Section: Doi: 101002/adma201605987mentioning
confidence: 99%